IMPLEMENTATION OF ZONING SYSTEM AND REGULATION OF TRAFFIC FLOW PATTERNS AT BANDAR SRI JUNJUNGAN CROSSING PORT OF DUMAI CITY - Surnata Surnata; Driaskoro Budi Shidarta; Sri Maya Arifa (IWTJ : International Water Transport Journal, 2021)
Bandar Sri Junjungan Port is a port that manages the Dumai - Tanjung Kapal track. This commercial trajectory connects between districts, namely Dumai City and Bengkalis Regency. In its daily activities, this port serves crossings as many as 8 trips / day with a crossing time of 45minutes. Based on the analysis conducted using survey data and also using several sources of legal foundation and theoretical foundation for zoning system improvement activities in this port, determination of land facilities, the determination of traffic flow patterns, and analysis of the placement of existing officers and signs, to provide improved service of service users because the growth rate of passengers is increasing. From the analysis can be concluded that the zoning system at Bandar Sri Junjungan Crossing Port, has not been implemented based on PM No. 29 of 2016 on Sterilization of Crossing Ports and SK.242 of 2010 on Port Traffic Management.